Effectiveness and Efficiency of the E-Filing System in Enhancing Taxpayer Compliance - Lannai, Darwis (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to evaluate the effectiveness and efficiency of the e-filing system in improving taxpayer compliance. The issue of taxpayer compliance is a significant concern in the field of taxation, especially in Indonesia, where taxpayer compliance remains relatively low. This is particularly alarming when compared to the growth of businesses in the country. As technology becomes increasingly integral to tax administration, understanding how the e-filing system affects taxpayer compliance is crucial. The study population consists of 130,000 taxpayers registered at KPP Pratama Makassar Utara. A sample of 100 taxpayers was selected using the Slovin formula. The research employed field research methods with quantitative data and primary data sources. Data were collected through a survey by distributing questionnaires to taxpayers. Data analysis was conducted using multiple linear regression with the aid of SPSS software. The results indicate that both the effectiveness and efficiency of the e-filing system have a positive and significant impact on taxpayer compliance. These findings provide important insights into how the e-filing system can motivate taxpayers to better fulfill their tax obligations, which in turn can enhance overall tax compliance and administrative efficiency.